A quantitative investigation of the effect of Mn segregation on microstructural properties of quenching and partitioning steels. (August 2017) - HajyAkbary, Farideh; Sietsma, Jilt; Petrov, Roumen H.; Miyamoto, Goro; Furuhara, Tadashi; Santofimia, Maria Jesus
Abstract: Quenching and partitioning (Q&P) process of a 0.3C-1.3Si-3.2Mn (wt%) steel with Mn segregation is studied experimentally and theoretically. During initial quenching a higher fraction of martensite forms in Mn-poor regions compared to Mn-rich regions. In the partitioning process, austenite in Mn-poor regions is surrounded with a higher fraction of martensite than austenite in Mn-rich regions and therefore receives a larger amount of carbon. When carbon partitioning is not sufficient to stabilize austenite, a higher fraction of martensite forms, during final quenching, in Mn-poor regions. Lowering the quenching temperature in the Q&P process reduces inhomogeneity in the distribution of phases. Graphical abstract: